KESEHATAN IBU DAN BAYI PADA PERNIKAHAN DINI - Ernawati, Hery; Verawati, Metti (Jurnal Media Ilmu Kesehatan, 2014)
Background: Marriage under the age of 20 (early marriage) can cause variety of problems, one of which effects on the health of the mothers and the babies. Objective: This study aimed to measure the health of mothers and babies in early-married women. Methods: This was a descriptive study with a retrospective design to investigate the health of mothers and babies who married in early age. This study was conducted in May to July 2014. Instruments used was a checklist filled out by researchers based on data from the respondents or through the existing data on Kartu Menuju Sehat (KMS). The maternal health was assessed during pregnancy, childbirth and postnatal period, and the infants health was assessed by the baby's condition at birth. Research was conducted at Ngrayun District. Samples were chosen purposively, resulted in 42 respondents. Data was analysed in univariate analysis. Results: Maternal health problems during pregnancy were anemia, dizziness and swelling during  pregnancy. Problems occured during labor time were prolonged labor for 15 hours, bleeding, and postpartum infection characterized by fever, pain and itching. Infants in early marriage were mostly healthy, there were only 2 infants born preterm and one with low birth weight. Conclusion: This study indicated the presence of maternal health problems during pregnancy, childbirth and post-partum, and most infants were in good health condition. There were only 2 babies born prematurely and with low birth weight. However, efforts to diminish numbers of early marriage are stil important, with the collaboration of relevant agencies. Keywords: Maternal health during pregnancy, childbirth, postpartum, baby health, early marriage.